Slow release of fragrance aldehydes and ketones in functional perfumery from dynamic mixtures generated with N‐heteroarylmethyl‐substituted secondary diamines. (27th May 2013) - Trachsel, Alain; Chapuis, Christian; Herrmann, Andreas
ABSTRACT Dynamic mixtures of aminals generated by reversible reaction of diamines with volatile aldehydes and ketones are suitable delivery systems to increase the long‐lastingness of fragrance perception in functional perfumery applications. N‐Heteroarylmethyl‐substituted secondary diamines of 1, 2‐diaminocyclohexane, 1, 3‐diaminocyclohexane, 1, 2‐diaminoethane, 1, 2‐diaminopropane, 1, 3‐diaminopropane or 2‐(aminomethyl)piperidine were prepared by reaction with furan‐, 1H‐pyrrole‐, thiophene‐ or pyridine‐2‐carbaldehyde and reduction of the intermediate imines with NaBH4. The performance of the delivery system was evaluated in a fabric softener application in the presence and absence of a diamine by following the evaporation of a mixture of 18 fragrance aldehydes and ketones on dry cotton using dynamic headspace analysis. Equilibration of the mixture in the presence of a diamine simultaneously increased the headspace concentrations of several fragrance raw materials above the cotton surface as compared to a reference sample without diamine. Equilibrated dynamic mixtures of diamines were found to be suitable delivery systems to prolong the evaporation of fragrance aldehydes and ketones in practical applications of functional perfumery. Copyright © 2013 John Wiley & Sons, Ltd.